2019
DOI: 10.1016/j.surg.2019.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism and transfusion after major abdominopelvic surgery

Abstract: Background: Thromboprophylaxis aims to reduce venous thromboembolism but has the potential to increase bleeding. We sought to evaluate the risk of venous thromboembolism and transfusion after major abdominopelvic procedures and to quantify the association of the procedure with venous thromboembolism. Methods: The American College of Surgeons' National Surgical Quality Improvement Program was queried for patients who received an abdominopelvic surgery between 2005 and 2016. Patient factors, operative factors, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…This may limit the results of the study, as the population may not represent the target audience. Finally, we used the Caprini score to stratify patients' risk of VTE for this PtDA; however, other factors such as specific procedure or length of procedure may impact patients' risk of VTE and may have been missed, as they are not included in the Caprini score 48,49 …”
Section: Discussionmentioning
confidence: 99%
“…This may limit the results of the study, as the population may not represent the target audience. Finally, we used the Caprini score to stratify patients' risk of VTE for this PtDA; however, other factors such as specific procedure or length of procedure may impact patients' risk of VTE and may have been missed, as they are not included in the Caprini score 48,49 …”
Section: Discussionmentioning
confidence: 99%
“…Postoperative bleeding varies by procedure, as well as bleeding definition. In the NSQIP database review by McAlpine et al, 18 the risk of bleeding (defined by transfusion requirement) in proctocolectomy cases ranges from 4.6% (laparoscopic colectomy) to 13.9% (open colectomy). Studies have reported bleeding risks of .9% to 4% with chemoprophylaxis but no significant increased risk with extended chemoprophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the duration of surgical operation showed a stronger predictive value for NHC than other variables, such as the duration from HVR to GI surgery and simple AVR. Other studies also have shown that the risk of venous thrombotic complications increases gradually with the length of surgery [McAlpine 2019]. Therefore, for patients whose operation time exceeds 160 minutes, the surgeon should be highly alert to postoperative complications and thrombotic complications, especially.…”
Section: E312mentioning
confidence: 99%